IMPLEMENTASI PEMBELAJARAN PARTISIPATIF BERBASIS TEKNOLOGI TEPAT GUNA DALAM PENDIDIKAN LINGKUNGAN - Prina Yelly; Iqbal Nuari (KARYA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Community reliance on commercial household cleaning products, coupled with the limited use of appropriate technology, indicates the need to improve knowledge, practical skills, and environmental awareness through participatory educational activities. This community service program aimed to implement participatory learning based on appropriate technology by training residents of Secanggang Village, Langkat Regency, Indonesia, in dishwashing liquid production. The program employed a participatory learning approach consisting of preparation, socialization, training, hands-on practice, evaluation, and mentoring. Learning activities were conducted through interactive lectures, demonstrations, group discussions, practical exercises, and reflective sessions to encourage active participation throughout the learning process. The results showed that participants understood the concept of appropriate technology, were able to produce dishwashing liquid independently in accordance with the demonstrated procedures, and demonstrated increased participation during the training activities. In addition to improving practical skills, the program enhanced environmental awareness and encouraged the application of simple technology to support environmentally friendly household practices. Therefore, participatory learning based on appropriate technology is an effective strategy for improving community knowledge, practical skills, and participation while promoting sustainable community empowerment.